This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The given equation is a Reciprocal Equation (also called Palindromic Equation ) as Co - efficient of z n = Co - efficient of z 1 1 − i , where i ϵ ( 0 , 1 , 2 , . . , 1 0 , 1 1 ) . Generally, a palindromic equation of degree n can be reduced to an equation of degree 2 n , where n is even, by making a substitution z + z 1 = t . But here n is odd, so we need to perform an additional step of manipulation which is as follows :- 4 z 1 1 + 4 z 1 0 − 2 1 z 9 − 2 1 z 8 + 1 7 z 7 + 1 7 z 6 + 1 7 z 5 + 1 7 z 4 − 2 1 z 3 − 2 1 z 2 + 4 z + 4 = 0 ⟹ ( z + 1 ) This can be reduced ! ( 4 z 1 0 − 2 1 z 8 + 1 7 z 6 + 1 7 z 4 − 2 1 z 2 + 4 ) = 0 . ( z + 1 ) gives z = − 1 . Now, considering, 4 z 1 0 − 2 1 z 8 + 1 7 z 6 + 1 7 z 4 − 2 1 z 2 + 4 = 0 . Dividing the entire equation by z 5 and then replacing z + z 1 by t , followed by simplification yields :- 4 t 5 − 4 1 t 3 + 1 0 0 t = 0 ⟹ t ( t 2 − 4 ) ( 4 t 2 − 2 5 ) = 0 ⟹ t = 0 , ± 2 , ± 2 5 ⟹ z + z 1 = 0 , ± 2 , ± 2 5 ⟹ z = -1 occurs here as well ± i , ± 1 , ± 2 1 , ± 2 . So, total number of distinct roots is 8 . Furthermore, 4 z 1 1 + 4 z 1 0 − 2 1 z 9 − 2 1 z 8 + 1 7 z 7 + 1 7 z 6 + 1 7 z 5 + 1 7 z 4 − 2 1 z 3 − 2 1 z 2 + 4 z + 4 = ( x − 2 ) ( x − 1 ) 2 ( x − i ) ( x + i ) ( x + 1 ) 3 ( x + 2 ) ( 2 x − 1 ) ( 2 x + 1 )